HUMAN RESOURCE SECURITY FRAMEWORK FOR COMPETITIVENESS IMPROVEMENT OF BUSINESS ENTITIES - SHANDOVA, Nataliia; MIESHKOVA-KRAVCHENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores theoretical and applied approaches to human resource security management in the context of growing economic turbulence. The focus is placed on the transformation of the role of HR security – from a narrowly functional protective tool to a strategic resource for enhancing the competitiveness of business entities. The study analyzes current scientific approaches to HR security and identifies three main management models: operational-defensive, functional-institutional, and strategically oriented. These models are compared based on key criteria such as management focus, types of threats, tools used, the role of personnel, and the level of adaptability. The necessity of developing an integrated model of human resource security management is substantiated. This model combines protective, analytical, socio-psychological, and strategic components into a unified system. The author presents a conceptual framework for the integrated model, which includes four functional blocks: analytical-forecasting, normative-organizational, socio-psychological, and value-strategic. The article details the implementation methodology and tools for formalizing the model, including a proposed indicative-rating approach for assessing the level of HR security, as well as a step-by-step methodology – from risk diagnostics to integration into the enterprise strategy. Special attention is given to recommendations for adapting the model to the specific needs of different sectors of the Ukrainian economy. It is found that the proposed model is flexible, scalable, and suitable for practical application in industry, the IT sector, healthcare, public administration, and small businesses. The integrated model can serve as a foundation for enterprise HR policy under crisis and post-crisis conditions, contributing to reduced staff turnover, increased internal trust, enhanced adaptability, and strengthened market positions. The results provide a basis for further empirical studies and the development of quantitative mechanisms for evaluating HR security effectiveness in a strategic context.